The Role Of Internal Financing Sources To Reduce Liquidity Risks: A Study Of A Sample Of Jordanian Islamic Banks - Muneeb Khalaf Mhameed; Ahmed Fareed Naji; Ali Hamad Ali (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
This study aims to analyze the impact of internal financing sources on liquidity risks in Jordanian Islamic banks during the period from 2008 to 2022, using regression analysis. The results show that increasing paid-in capital, reserves, and retained earnings reduces liquidity risk and enhances financial stability. It has been shown that Islamic banks are able to manage these resources effectively. The study recommends strengthening these sources and applying advanced risk management procedures that are compatible with Sharia controls.